Dual Anti-cancer and Anti-Itch Activity of PD176252 Analogues: Design, Synthesis and Biological Evaluation - Yu, Ming-Jun; Yao, Sen; Li, Ting-Ting; Yang, Rui; Yao, Ri-Sheng (Anti-Cancer Agents in Medicinal Chemistry, 2019)
Background: Cancer patients treated with targeted anti-cancer drug suffer from itch or pruritus. Itch or pruritus is an unpleasant sensation that brings about a negative impact on quality of life, and serious itch may lead to dose reduction and even discontinuation. Gastrin releasing peptide receptor (GRPR) plays a critical role in itch, inflammation and cancer, and GRPR antagonist has obvious effect on cancer, inflammation and itch. The aim of this paper is to develop a new agent with anti-cancer and anti-itch activity. Methods: A series of GRPR antagonist PD176252 analogues (3a-3l) were designed and synthesized. Both anticancer and anti-itch activities were evaluated. Anti-cancer activity was evaluated in three human cancer cell lines in vitro, the anti-itch activity in evaluated with Kunming mice by intrathecal injection of chloroquine phosphate as a modeling medium. And the cytotoxicity on normal cells was evaluated. Results: Of the tested compounds, compound 3i showed potently anti-cancer activity to all cancer cell lines tested with IC50 values of 10.5μM (lung), 11.6μM (breast) and 12.8μM (liver) respectively and it also showed significant inhibition of the scratching behavior. Comparing with PD17625, compound 3i and 3g gave better inhibition activities against all cancer cell lines, compound 3b, 3c and 3i showed better anti-itch activity. The compound 3i is safe for normal breast and liver normal cells, but it has high cytotoxicity on normal lung cell. Conclusion: The synthesized compounds have dual anti-cancer and anti-itch activity, so the development of drug with dual anti-tumor and anti-itch property is possible.
Keywords: anti-cancer